2024
DOI: 10.1007/s11111-024-00448-5
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and school absences: evidence from England

Risto Conte Keivabu

Abstract: Extreme temperature affects children’s health, cognitive abilities, and behavior with implications for human capital accumulation. For example, several studies documented both heat and cold to decrease cognitive abilities and being consequential for test scores. An alternative, less explored pathway, by which temperature is consequential for educational achievement, is absenteeism. In this study, we explore how heat affects school attendance leveraging administrative data on more than 22,000 schools in England… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“… 1 , 2 Previous studies showed extreme temperatures (i.e., out of comfort), especially heat, to increase the incidence of negative health outcomes such as morbidity 3 and mortality. 4 , 5 Additionally, studies exposed extreme temperatures to be deleterious also for a large array of other health related outcomes, affecting expressed sentiment, 6 , 7 , 8 externalizing behavior, 9 , 10 , 11 , 12 cognitive performance of students and office workers, 13 , 14 , 15 , 16 , 17 , 18 , 19 learning, 20 , 21 time allocation, 22 absenteeism, 23 , 24 hate speech, 25 decision making, 26 and manual labor productivity. 23 , 27 In this article, we leverage information on parliamentary speeches to focus on one of these outcomes: language complexity (which could serve as a potential proxy for cognitive performance).…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 Previous studies showed extreme temperatures (i.e., out of comfort), especially heat, to increase the incidence of negative health outcomes such as morbidity 3 and mortality. 4 , 5 Additionally, studies exposed extreme temperatures to be deleterious also for a large array of other health related outcomes, affecting expressed sentiment, 6 , 7 , 8 externalizing behavior, 9 , 10 , 11 , 12 cognitive performance of students and office workers, 13 , 14 , 15 , 16 , 17 , 18 , 19 learning, 20 , 21 time allocation, 22 absenteeism, 23 , 24 hate speech, 25 decision making, 26 and manual labor productivity. 23 , 27 In this article, we leverage information on parliamentary speeches to focus on one of these outcomes: language complexity (which could serve as a potential proxy for cognitive performance).…”
Section: Introductionmentioning
confidence: 99%